Reforming legal education in Pakistan by introducing practical aspects in the current syllabus at the law schools and enhancing compulsory program during pupillage period - Dastagir, Ghulam; Ambaras Khan, Hanna; Hussain, Faridah; Abdul Hak, Nora; Abdul Wahab, Mohd. Iqbal (2019)
Teaching method in law schools should facilitate law students with an understanding of legal principles and concepts. Besides, during the studies law students should be able to apply the relevant legal knowledge and skills to solve legal problems. On top of that, the students should be able to demonstrate good drafting and advocacy skills. The challenges facing by legal education in Pakistan is the tendency of maintaining the earlier methods of teaching without making changes for many years which affected the institutions of the country being weakened, and thereafter facing crisis in legal education as highlighted by the Supreme Court of Pakistan’s recent judgment. Therefore, the stakeholders are expected to make in supporting the order of the Court to revamp and enhance the current legal education. This paper aims to compare the mode of teaching, assessments, and examinations at the law schools in Pakistan and Malaysia by adopting qualitative method and comparative analysis. Besides, syllabus in the law schools in Pakistan and Malaysia are analysed. It is found that the Malaysian universities stressed the practical aspect to the law students. This research will recommend that the syllabus, the method of teaching, assessment and examination, needs to be reformed by looking at the Malaysian practice. The enhancement includes to have a compulsory Legal Attachment Program (“LAP”), revising the final year’s syllabus by including vocational and clinical legal practice subjects in preparing the students for pupillage, to introduce Alternative Dispute Resolution subject in providing skills to resolve dispute through non-adversarial method and to introduce compulsory mooting as part of adversarial skills. The new method will promote the development of the critical thinking and problem-solving skills, team skills, ethics and professionalism for competent lawyers in Pakistan. The paper further suggests that the Pakistan Bar Council to introduce strict ethic’s course for pupil and a legal aid program.